Solar cell and preparation process thereof, laminated cell, photovoltaic module
Patent Information
- Application Number
- CN202611443133.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本申请实施例提供一种太阳能电池及其制备工艺、叠层电池、光伏组件,以解决现有技术中光伏组件的成本高,且HF10衰减率和转换效率不能兼顾的问题,至少有利于改善太阳能电池的光电转换效率
[0015]本申请实施例提供的技术方案至少具有以下优点:本发明在导电银浆中引入包括二氧化锆、二氧化钛、氮化钛和碳化钛的稳定剂组合物,二氧化锆的物化性能稳定,使得组件能在高温环境下保持结构稳定,其形成的纤维形态具有高抗热震性,能够在温度变化中维持完整性。氮化钛与碳化钛的加入可为栅线提供结构支撑,增强栅线与电池基底之间的结合强度,从而减少栅线脱落。稳定剂组合物各组分的协同能够通过增强浆料体系的机械强度和耐热性能来抑制光伏组件在湿热环境下的功率衰减,从而能够在不采用高成本胶膜的前提下显著提升光伏组件的长期稳定性,实现低成本、低衰减与高转换效率的兼顾。
Smart Images

Figure CN122995326A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the photovoltaic field, and in particular to a solar cell and its manufacturing process, a tandem cell, and a photovoltaic module. Background Technology
[0002] In the fabrication of solar cells, after a conductive paste is printed onto the cell substrate, it needs to be cured to form initial grid lines, followed by sintering to obtain the final solar cell. This conductive paste is typically composed of components such as silver powder, glass powder, and organic carrier. The sintering process allows the silver powder to form good ohmic contact with the cell surface, thereby collecting photocurrent.
[0003] However, existing photovoltaic (PV) modules often face significant challenges when dealing with humid and hot environments (such as 85°C and 85%RH). To reduce the HF10 degradation rate of modules, current technologies typically employ the addition of expensive materials such as high-cost encapsulants for protection. While this traditional solution can improve degradation performance to some extent, it significantly increases the production cost of PV modules. Furthermore, the use of high-cost encapsulants may affect the light transmittance or electrical performance of the solar cells, making it difficult to simultaneously maintain high efficiency and low degradation rates, resulting in both high cost and performance degradation. Summary of the Invention
[0004] This application provides a solar cell and its fabrication process, a tandem cell, and a photovoltaic module to solve the problems of high cost of photovoltaic modules in the prior art, and the inability to simultaneously achieve HF10 degradation rate and conversion efficiency, which at least helps to improve the photoelectric conversion efficiency of solar cells.
[0005] According to some embodiments of this application, one aspect of this application provides a process for fabricating a solar cell, including: printing a conductive paste on a cell substrate; curing the conductive paste to form initial grid lines; sintering the initial grid lines to obtain a solar cell; wherein the conductive paste includes silver powder, glass powder, an organic carrier, and a stabilizer composition; the stabilizer composition includes zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide; wherein the weight ratio of zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide is (1~2):(1~2):(0.5~1.5):1.
[0006] In some embodiments, the BET specific surface area of titanium carbide in the stabilizer composition is 8-25 m². 2 / g; The BET specific surface area ratio of zirconium dioxide, titanium dioxide, titanium nitride and titanium carbide is (0.23~0.8):(0.13~1.2):(0.2~0.6):1.
[0007] In some embodiments, the stabilizer composition in the conductive paste is a mixture of particles of each component with a particle size Dv50 of 0.3~2.5μm; the ratio of the stabilizer composition to the silver powder particle size Dv50 is (0.15~0.6):1.
[0008] In some embodiments, the conductive paste comprises, by weight, 70-90 parts of silver powder, 3-10 parts of glass powder, 8-20 parts of organic carrier, and 0.5-1.5 parts of a stabilizer composition.
[0009] In some embodiments, the glass powder comprises 50-65% PbO, 13-28% TeO2, 6-14% B2O3 and 2-8% SiO2, based on a molar percentage content of 100%.
[0010] In some embodiments, the molar ratio of PbO to zirconium dioxide in the glass powder is (6~18):1; the molar ratio of TeO2 to zirconium dioxide is (2~8):1.
[0011] In some embodiments, the curing process is thermal curing at a temperature of 180~260°C for 0.5~3 hours; and / or, the sintering temperature is 200~900°C for 3~60 seconds; and / or, when the stabilizer composition in the conductive paste is 0.9~1.5 parts by weight, the sintering temperature is 780~860°C; and / or, when the stabilizer composition in the conductive paste is greater than or equal to 0.5 parts and less than 0.9 parts by weight, the curing temperature is 200~250°C.
[0012] According to some embodiments of this application, one aspect of this application provides a solar cell, which is prepared by the above-described solar cell preparation process.
[0013] According to some embodiments of this application, one aspect of this application provides a stacked battery, which includes a top battery and a bottom battery, wherein the bottom battery is the aforementioned solar cell.
[0014] According to some embodiments of this application, one aspect of this application provides a photovoltaic module, including: a battery string, which is formed by connecting multiple solar cells or stacked cells as described above; an encapsulating film for covering the surface of the battery string; and a cover plate for covering the surface of the encapsulating film facing away from the battery string.
[0015] The technical solution provided in this application has at least the following advantages: The present invention introduces a stabilizer composition comprising zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide into the conductive silver paste. Zirconia has stable physicochemical properties, enabling the module to maintain structural stability at high temperatures. The resulting fiber morphology exhibits high thermal shock resistance, maintaining integrity under temperature variations. The addition of titanium nitride and titanium carbide provides structural support for the grid lines, enhancing the bonding strength between the grid lines and the battery substrate, thereby reducing grid line detachment. The synergistic effect of the stabilizer composition components can suppress power degradation of photovoltaic modules in humid and hot environments by enhancing the mechanical strength and heat resistance of the paste system. This significantly improves the long-term stability of photovoltaic modules without using high-cost encapsulant films, achieving a balance between low cost, low degradation, and high conversion efficiency. Attached Figure Description
[0016] One or more embodiments are illustrated by way of example with reference to the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the drawings in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 A schematic diagram of the structure of a solar cell according to an embodiment of this application is shown.
[0018] The above figures include the following reference numerals:
[0019] 101. Silicon substrate; 102. Front passivation layer; 103. Front gate line; 104. Back passivation layer; 105. Tunneling oxide layer; 106. n+ polysilicon layer; 107. p+ emitter. Detailed Implementation
[0020] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0021] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0022] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent three cases: A exists, A and B exist simultaneously, and B exists. In addition, the character " / " in this document generally indicates that the related objects before and after it have an "or" relationship.
[0023] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0024] In the description of the embodiments of this application, unless otherwise expressly specified and limited, the technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0025] In the description of the embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and other components may be further included. Furthermore, when a component such as a layer, film, region, or plate is referred to as being "on / located" on another component, it can be "directly on" the other component (i.e., located on the surface of the other component with no other components between them), or another component may be present therein. Moreover, when a component such as a layer, film, region, or plate is "directly located" on another component, or when a component such as a layer, film, region, or plate is located on the surface of another component, it indicates that no other components are located therein.
[0026] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "part" is also intended to include the plural form unless the context clearly indicates otherwise. Components include layers, films, regions, or plates, etc.
[0027] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. Those skilled in the art will understand that many technical details have been provided in the various embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.
[0028] As is known from the background art, existing photovoltaic modules suffer from high costs and a trade-off between HF10 degradation rate and conversion efficiency. To address these issues, this application provides a solar cell fabrication process, comprising: printing a conductive paste onto a cell substrate; curing the conductive paste to form initial grid lines; and sintering the initial grid lines to obtain a solar cell. The conductive paste comprises silver powder, glass powder, an organic carrier, and a stabilizer composition. The stabilizer composition comprises zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide. The weight ratio of zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide is (1~2):(1~2):(0.5~1.5):1.
[0029] This invention improves the structural stability and resistance to damp heat of solar cell electrode grid lines by introducing a stabilizer composition consisting of zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide into the conductive paste. Zirconium dioxide and titanium dioxide possess high-temperature stability and chemical inertness, forming a dense protective barrier at the grid line interface after sintering, preventing external corrosive media from eroding the silver grid lines. Titanium nitride and titanium carbide, as high-strength structural support phases, are embedded in the paste network, enhancing the mechanical strength of the grid lines and their adhesion to the cell substrate. The four components interpenetrate at the microscale, constructing a dual stabilization system of chemical passivation protection and mechanical structural enhancement. This allows the grid lines to maintain interface integrity under high-temperature and high-humidity environmental stress, reducing power decay in HF10 testing and avoiding the negative impact of using high-cost encapsulation materials on cell conversion efficiency.
[0030] In the aforementioned stabilizer composition, zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide are present in a defined weight ratio. The relative amounts of zirconium dioxide and titanium dioxide form a continuous and effective chemically inert protective layer, while the amounts of titanium nitride and titanium carbide provide microstructural support. Adjusting these two components to the aforementioned ratio ensures uniform dispersion of each component in the slurry, preventing agglomeration or deterioration of rheological properties caused by excessive component content. This weight ratio facilitates the wetting and bonding of the glass phase and metal particles during sintering, allowing the stabilizer components to fill the gaps between silver particles and interface defects, enhancing the overall density and corrosion resistance of the grid lines, and achieving a balance between low-cost manufacturing of photovoltaic modules and low attenuation rates and high conversion efficiency.
[0031] This invention utilizes a conductive paste incorporating the aforementioned stabilizer composition for the fabrication of solar cells. First, the conductive paste is printed onto a battery substrate and cured. The zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide microparticles in the stabilizer composition are uniformly dispersed within a matrix composed of silver powder, glass powder, and an organic carrier. At this stage, the high-melting-point zirconium dioxide and titanium dioxide particles remain in a solid, dispersed state, while the titanium nitride and titanium carbide particles are embedded in the gaps between the silver particles. During curing, the particles of each component in the stabilizer composition remain uniformly dispersed within the organic carrier of the paste. Due to their high melting points (2715℃ and 1843℃, respectively) and strong chemical inertness, zirconium dioxide and titanium dioxide do not undergo phase transformation during curing. They are embedded in the gaps between the silver powder particles and the organic resin network in solid microparticle form, acting as steric hindrance stabilizers and effectively inhibiting the pre-agglomeration and migration of silver particles before subsequent high-temperature sintering. Titanium nitride (TiN) and titanium carbide (TiC) particles serve as hard structural support points, anchoring at the silver powder-organic carrier network interface in the semi-solid gate line preform formed after curing. This enhances the structural integrity of the gate line preform, provides a stable skeletal precursor for the sintering stage, and yields the initial gate line.
[0032] Then, the initial grid lines undergo sintering, where glass powder melts to form a glass phase that impregnates silver particles and stabilizer particles. The stabilizer composition and glass powder exhibit a significant synergistic effect. During the sintering and melting stage, PbO in the glass powder forms a low-melting-point glass phase, impregnating the silver particles and the battery substrate surface, filling interparticle pores, and reducing interfacial energy. Silver powder undergoes neck growth and densification through surface diffusion and grain boundary diffusion mechanisms, forming a continuous silver conductive network. Meanwhile, zirconium dioxide and titanium dioxide particles in the stabilizer composition remain solid-dispersed within the glass phase, acting as a second-phase particle pinning mechanism, inhibiting excessive flow of the glass phase and Ostwald ripening of the silver particles, thereby refining the grid line microstructure. Simultaneously, titanium nitride and titanium carbide undergo micro-regional solid solution reactions with silicon dioxide in the glass phase at the interface, forming a Ti-O-Si bridging structure, which significantly enhances the chemical bonding strength between the glass phase and the metal compound particles, significantly improving the overall peel resistance of the grid lines. Meanwhile, zirconium dioxide and titanium dioxide, with their high chemical inertness and high melting point, maintain a solid framework in the glass phase, and zirconium dioxide retains a fibrous morphology at the microscopic level, providing excellent thermal shock resistance. Titanium nitride and titanium carbide, as high-strength phases, are embedded in the silver-glass composite structure, enhancing the mechanical anchoring force at the interface and reducing microcracks in the gate lines caused by thermal stress. Ultimately, a stable structure is formed at the gate-substrate interface, consisting of a chemical passivation protective layer of ZrO2 / TiO2 and a mechanically reinforcing framework of TiN / TiC, effectively preventing moisture and corrosive media from penetrating into the battery, maintaining the stability of the interfacial electrical contact, and thus maintaining low degradation characteristics during device service.
[0033] In one embodiment of this application, the BET specific surface area of titanium carbide in the stabilizer composition is 8-25 m². 2 / g; the BET specific surface area ratio of zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide is (0.23~0.8):(0.13~1.2):(0.2~0.6):1. Titanium carbide with a BET specific surface area within the above range is more easily dispersed uniformly in the slurry, thereby promoting the formation of a dense and uniform interface after sintering, further improving the mechanical strength of the grid lines and the long-term stability of the module.
[0034] Limiting the specific surface area ratio of each component in the stabilizer composition to the above range can further promote the uniform micro-dispersion of each metal compound particle in the slurry system, and make it easier for components with different specific surface area characteristics to form a dense and stable interfacial contact state. This is beneficial to improving the mechanical strength of the grid structure and the bonding strength with the battery substrate, thereby further improving the long-term reliability performance of solar cells in humid and hot environments.
[0035] In one embodiment of this application, the stabilizer composition in the conductive paste is a mixture of particles of each component with a particle size Dv50 of 0.3~2.5μm; the ratio of the stabilizer composition to the silver powder particle size Dv50 is (0.15~0.6):1. When the stabilizer composition has a particle size Dv50 within the above range, it is easier to uniformly disperse in the gaps between the silver powder particles, thereby more easily promoting the formation of a dense interface after sintering, improving the grid line bonding force and the long-term stability of the component.
[0036] By adjusting the stabilizer composition and silver powder particle size to the above ratio, the particle size matching degree between the stabilizer composition and silver powder at the microscale can be further improved. This makes it easier for the stabilizer particles to fill the gaps and interfaces between the silver particles evenly, which is beneficial to optimizing the printing rheological properties of the paste. In turn, it helps to enhance the ability of the grid lines to resist thermal stress and environmental erosion after sintering, and promotes the reduction of HF10 decay rate.
[0037] To further enhance the balance and synergistic effect among the components of the conductive paste, in one embodiment of this application, the conductive paste comprises, by weight, 70-90 parts of silver powder, 3-10 parts of glass powder, 8-20 parts of organic carrier, and 0.5-1.5 parts of a stabilizer composition. Proportioning the raw materials of the conductive paste in the above-mentioned proportions is more conducive to maintaining the integrity of the silver powder conductive network and the rheological stability of the organic carrier while providing structural support and reducing degradation, thereby better achieving a good balance between battery conversion efficiency and low degradation performance.
[0038] In one embodiment of this application, the glass powder comprises 50-65% PbO, 13-28% TeO2, 6-14% B2O3, and 2-8% SiO2, based on a 100% molar percentage content. The glass powder raw materials in the above proportions can further optimize the melting characteristics and wetting behavior of the conductive paste during sintering, making it easier for the glass powder to form a uniform protective layer on the silver powder particles and the surface of the battery substrate. This facilitates the control of the thermal expansion coefficient matching between the paste and the substrate, thereby helping to reduce the generation of interfacial microcracks and improve the long-term operational stability of the solar cell.
[0039] To further optimize the high-temperature rheological properties and chemical compatibility of the slurry, in one embodiment of this application, the molar ratio of PbO to zirconium dioxide in the glass powder is (6~18):1; and the molar ratio of TeO2 to zirconium dioxide is (2~8):1. Adjusting the proportions of the components in the glass powder to zirconium dioxide within the above range is beneficial for promoting a more stable interfacial bond between zirconium dioxide and the glass phase during subsequent sintering, enhancing the anchoring effect of the grid lines on the glass matrix, effectively suppressing grid line corrosion and detachment caused by moisture erosion in the HF10 test, thereby significantly improving the long-term damp heat resistance stability of the module and achieving a better degradation suppression effect than simply adding zirconium dioxide.
[0040] In some embodiments, the curing process is thermosetting at a temperature of 180-260°C for 0.5-3 hours; and / or, sintering at a temperature of 200-900°C for 3-60 seconds; and / or, when the stabilizer composition in the conductive paste is 0.9-1.5 parts by weight, the sintering temperature is 780-860°C; and / or, when the stabilizer composition in the conductive paste is greater than or equal to 0.5 parts and less than 0.9 parts by weight, the curing temperature is 200-250°C. In some embodiments, the curing process is UV curing, wherein the UV curing light type is one or more of 365nm, 395nm, and 405nm, and the UV curing power is 800-2500mW / cm². 2 The duration is 15~90s.
[0041] The above-mentioned process conditions can further balance the dispersion stability of the stabilizer in the slurry and the interfacial bonding strength during the sintering process, thereby helping to ensure good adhesion of the silver wires to the cell surface and optimize the carrier transport path, thus improving the consistency of solar cell fabrication and the final photoelectric conversion performance.
[0042] In some embodiments, the organic carrier contains an organic resin comprising ethyl cellulose and / or an acrylic resin; and / or a solvent comprising one or more of diethylene glycol butyl ether acetate, diethylene glycol monobutyl ether acetate, and terpineol; and / or a thixotropic agent comprising hydrogenated castor oil and / or polyamide wax.
[0043] In another typical embodiment of this application, a solar cell is provided, which is prepared by the solar cell fabrication process described above. The solar cell prepared using the conductive paste defined in this application exhibits superior interfacial stability in its grid structure due to the synergistic effect of zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide. This improves the electrical contact stability of the cell during long-term service, reduces the increase in series resistance caused by interfacial degradation, maintains a high fill factor and conversion efficiency, and suppresses power decay.
[0044] In some embodiments, the solar cell includes a silicon substrate 101, a p+ emitter 107 and a front passivation layer 102 located on the front side of the silicon substrate, a tunneling oxide layer 105 and an n+ polycrystalline silicon layer 106 located on the back side of the silicon substrate, a back passivation layer 104, and an electrode (including a front grid line 103) located on the surface of the front passivation layer 102. The front grid line 103 is prepared by the conductive paste provided in the embodiments of this application using the preparation method provided in the embodiments of this application.
[0045] In another typical embodiment of this application, a tandem battery is provided, comprising a top cell and a bottom cell, wherein the bottom cell is the aforementioned solar cell. Based on the aforementioned solar cell, the bottom cell of the tandem battery exhibits superior resistance to damp heat, thereby enhancing the long-term reliability of the tandem battery in complex environments, making it particularly suitable for large-scale applications of high-efficiency tandem technology.
[0046] In another typical embodiment of this application, a photovoltaic module is provided, comprising: a battery string, formed by connecting multiple solar cells or stacked cells as described above; an encapsulating film for covering the surface of the battery string; and a cover plate for covering the surface of the encapsulating film facing away from the battery string.
[0047] Because the cell strings within the photovoltaic module's encapsulation structure possess the aforementioned low-attenuation characteristics, the overall anti-aging capability of the module can be significantly improved. The cell strings protected by the encapsulation film and cover plate exhibit lower power loss in stringent tests such as HF10, maintaining the stability of the module's output power. Simultaneously, the stable grid structure reduces the risk of hot spot effects, enhances the module's mechanical strength and electrical safety in harsh environments such as humidity, heat, and high salt spray, extends the effective service life of the photovoltaic system, reduces operation and maintenance costs, and improves the overall economic efficiency and reliability of the photovoltaic energy system.
[0048] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0049] Example 1
[0050] A solar cell includes a conductive paste suitable for the front grid lines of a TOPCon cell;
[0051] 1. Preparation of conductive paste
[0052] 1.1 Stabilizer Composition
[0053] Zirconium dioxide, titanium dioxide, titanium nitride and titanium carbide were mixed to obtain a stabilizer composition. The physicochemical properties of each component are shown in Table 1 and the addition ratio is shown in Table 2.
[0054] 1.2 Glass powder
[0055] The raw materials for glass powder were mixed and melt-quenched at 900℃ for 2 hours, and then ball-milled until Dv50 was 1.0μm to obtain glass powder; the proportions of the raw materials for glass powder are shown in Table 2.
[0056] 1.3 Preparation of conductive paste
[0057] Organic resin (ethyl cellulose, ETHOCEL™ Std 45, Dow), solvent (diethylene glycol butyl ether acetate, Butyl Carbitol™ Acetate), and thixotropic agent (hydrogenated castor oil, THIXCIN® R, Elementis) were mixed evenly to obtain an organic carrier. A composition of silver powder, glass powder, and stabilizer was premixed, and the organic carrier was added. The mixture was then thoroughly mixed in a planetary mixer. The mixture was transferred to a three-roll mill for rolling, and rolled six times until the slurry fineness was ≤5μm. After the fineness was qualified, vacuum defoaming and filtration were performed to obtain a conductive slurry. The weight proportions of each component in the above conductive slurry are shown in Table 3.
[0058] 2. Fabrication of solar cells
[0059] Step B1: Print the above conductive paste on the front side of the N-type TOPCon (tunneling oxide passivated contact) solar cell, dry it at 200°C for 1 hour to complete the curing and form the initial grid lines; wherein, the N-type TOPCon (tunneling oxide passivated contact) solar cell includes a cell substrate (silicon wafer), a passivation layer (tunneling oxide layer) and an emitter.
[0060] Step B2: Sintering is carried out in a sintering furnace at a peak temperature of 800℃ for 50 seconds at a belt speed of 4000 mm / min to obtain sintered solar cells. These cells are then assembled to form a solar cell. A schematic diagram of the structure is shown below. Figure 1 .
[0061] Examples 2 to 4
[0062] The difference from Example 1 is that the molar ratio of each raw material in the glass powder and the weight ratio of each component in the stabilizer composition are different, as shown in Table 2.
[0063] Example 5
[0064] The difference from Example 1 is that the weight proportions of each component of the conductive paste are different, as shown in Table 3;
[0065] In step B2, the sintering temperature is 780℃.
[0066] Example 6
[0067] The difference from Example 1 is that the weight proportions of each component of the conductive paste are different, as shown in Table 3;
[0068] In step B2, the sintering temperature is 250℃.
[0069] Example 7
[0070] The difference from Example 1 is that the weight proportions of each component of the conductive paste are different, as shown in Table 3;
[0071] In step B2, the sintering temperature is 200℃.
[0072] Example 8
[0073] The difference from Example 1 is that the weight proportions of each component of the conductive paste are different, as shown in Table 3;
[0074] In step B2, the sintering temperature is 860℃.
[0075] Example 9
[0076] The difference from Example 1 is that the BET specific surface area and particle size of each component of the conductive paste are different, as shown in Table 1; the curing temperature is 180°C and the curing time is 3 hours.
[0077] Example 10
[0078] The difference from Example 1 is that the BET specific surface area and particle size of each component of the conductive paste are different, as shown in Table 1; the curing temperature is 260℃ and the time is 0.5h.
[0079] Comparative Example 1
[0080] The difference from Example 1 is that no stabilizer composition is added to the conductive paste.
[0081] Comparative Example 2
[0082] The difference from Example 1 is that zirconium dioxide and titanium carbide are not added to the stabilizer mixture.
[0083] Test methods
[0084] The solar cells obtained from the embodiments of the present invention and the comparative examples were tested as follows, and the results are shown in Table 4.
[0085] 1. HF10 Power Degradation: The test was conducted according to the MQT 13 damp heat test specification of standard IEC 61215-2:2021. The photovoltaic modules were placed in a constant temperature and humidity test chamber (model ESPEC AR-5200LH) with environmental conditions set at 85℃ and 85% relative humidity for 1000 hours. During the test, the modules were removed from the test chamber every 200 hours and allowed to cool naturally to room temperature. The output power of the modules was then measured using IV characteristic testing equipment. The power degradation rate was calculated by comparing the initial power with the power at each stage of the test.
[0086] 2. Photoelectric conversion efficiency: Measured according to standard IEC 60904-1:2020, using AM1.5G spectrum at 25±1℃ and irradiance of 1000 W / m². 2 The test used a solar simulator (model WACOM WXS-155S-L2) in conjunction with an IV test system to scan the current-voltage characteristics of solar power under illumination and calculate the photoelectric conversion efficiency.
[0087] Table 1
[0088]
[0089] Table 2
[0090]
[0091] Table 3
[0092]
[0093] Table 4
[0094]
[0095] As can be seen, Comparative Example 1, lacking the stabilizer composition, resulted in a lack of chemical passivation and mechanical reinforcement at the interface of the silver grid after sintering. During the HF10 damp heat aging test, moisture could rapidly penetrate along the grain boundaries and interface defects of the silver particles, leading to grid corrosion and interface debonding, a significant increase in series resistance, and severe power attenuation (approximately 6.5%). Simultaneously, the degradation of the grid structure resulted in a decrease in carrier collection efficiency, causing the photoelectric conversion efficiency to be lower than that of the embodiments in this scheme. Comparative Example 2, without the addition of zirconium dioxide and titanium carbide, although TiO2 and TiN provided certain chemical stability and structural reinforcement, lacked the fibrous, highly thermally shock resistant framework of ZrO2 and the high-hardness core support of TiC, resulting in an incomplete stabilization system. TiO2 alone could not form a continuous chemically inert protective layer; TiN alone exhibited a rapid surface oxidation rate in high-temperature and high-humidity environments, leading to insufficient long-term stability. Therefore, although the HF10 attenuation rate of Comparative Example 2 (approximately 5.2%) was better than that of Comparative Example 1, it was still significantly higher than that of the embodiments containing the complete four-component stabilizer composition.
[0096] Therefore, this invention introduces a stabilizer composition comprising zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide into the conductive silver paste. The stable physicochemical properties of zirconium dioxide allow the module to maintain structural stability at high temperatures, and the resulting fiber morphology exhibits high thermal shock resistance, maintaining integrity under temperature variations. The addition of titanium nitride and titanium carbide provides structural support for the grid lines, enhancing the bonding strength between the grid lines and the cell substrate, thereby reducing grid line detachment. The synergistic effect of the stabilizer composition components can suppress power degradation of photovoltaic modules in humid and hot environments by enhancing the mechanical strength and heat resistance of the paste system. This significantly improves the long-term stability of photovoltaic modules without using high-cost encapsulant films, achieving a balance between low cost, low degradation, and high conversion efficiency.
[0097] Furthermore, it can be seen that the overall effect is better when all process parameters are within the preferred range of the present invention.
[0098] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.
Claims
1. A process for fabricating a solar cell, characterized in that, include: A conductive paste is printed on a battery substrate; the conductive paste is cured to form initial grid lines; the initial grid lines are sintered to obtain the solar cell; wherein... The conductive paste comprises a composition of silver powder, glass powder, organic carrier, and stabilizer. The stabilizer composition includes zirconium dioxide, titanium dioxide, titanium nitride, and titanium carbide; The weight ratio of zirconium dioxide, titanium dioxide, titanium nitride and titanium carbide is (1~2):(1~2):(0.5~1.5):
1.
2. The fabrication process of the solar cell according to claim 1, characterized in that, In the stabilizer composition The BET specific surface area of the titanium carbide is 8~25m². 2 / g; The BET specific surface area ratio of the zirconium dioxide, titanium dioxide, titanium nitride and titanium carbide is (0.23~0.8):(0.13~1.2):(0.2~0.6):
1.
3. The fabrication process of the solar cell according to claim 1 or 2, characterized in that, In the conductive paste The stabilizer composition is a mixture of particles of each component, with a particle size Dv50 of 0.3~2.5μm; The ratio of the stabilizer composition to the particle size Dv50 of the silver powder is (0.15~0.6):
1.
4. The fabrication process of the solar cell according to claim 1 or 2, characterized in that, The conductive paste comprises, by weight, 70-90 parts of the silver powder, 3-10 parts of the glass powder, 8-20 parts of the organic carrier, and 0.5-1.5 parts of the stabilizer composition.
5. The fabrication process of the solar cell according to claim 1 or 2, characterized in that, Based on a 100% molar percentage content of glass powder, the glass powder comprises 50-65% PbO, 13-28% TeO2, 6-14% B2O3, and 2-8% SiO2.
6. The fabrication process of the solar cell according to claim 5, characterized in that, In the glass powder The molar ratio of PbO to zirconium dioxide is (6~18):1; The molar ratio of TeO2 to zirconium dioxide is (2~8):
1.
7. The fabrication process of the solar cell according to claim 1 or 2, characterized in that, The curing process is thermosetting, with a temperature of 180~260℃ and a time of 0.5~3 hours; and / or, The sintering temperature is 200~900℃, and the time is 3~60s; and / or, When the stabilizer composition in the conductive paste is 0.9 to 1.5 parts by weight, the sintering temperature is 780 to 860°C; and / or, When the stabilizer composition in the conductive paste is greater than or equal to 0.5 parts and less than 0.9 parts by weight, the curing temperature is 200~250℃.
8. A solar cell, characterized in that, The solar cell is prepared by the solar cell preparation process described in any one of claims 1 to 7.
9. A stacked battery, the stacked battery comprising a top battery and a bottom battery, characterized in that, The bottom battery is the solar cell described in claim 8.
10. A photovoltaic module, characterized in that, include: A battery string is formed by connecting multiple solar cells as described in claim 9, or stacked cells as described in claim 9. An encapsulating film is used to cover the surface of the battery string; as well as A cover plate is used to cover the surface of the encapsulating film that faces away from the battery string.